Witloof chicory (Cichorium intybus L. var. foliosum) as a vegetable crop in South Africa - Konig, Roman (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Agic.) -- University of Stellenbosch, 1999.